(untitled) (PerCursos, 2021)
This paper aims to investigate the symbolical effectiveness of the Shamanism concerning the cure of its subjects and to raise questions about the silence of these natives in favor of scientific cure practices (power cures). We have the methodological support from the Discourse Analysis, which studies the language not only in its linguistic form, but also in its relation with the social — the extralinguistic. The method is going to involve a discursive analysis into some interviews, as well as in the ways of transmission and practices of the shamanic ritual that occur in the Amazon region through excerpts extracted from three online portals: Portal Mongabai, National Geographic, and G1. Our objective was to identify the resistance and existence of this practice in contemporaneity, even with its subjugation and disregard in order to comply with the cure practices brought by the eurocolonialism’s empirical sources, namely science and religion. The results show that the indigenous people endure the silencing and disregard because they do not have access to hospitals, since the COVID-19 is a new disease and demands specific treatments. For that purpose, we used theoretical-methodological subsidies from the Discourse Analysis, particularly the silencing concept in Orlandi (2009), and about the shamanic practices, we had the support of Maués (1994, 2007).